Corrected evaluation of the breech presentation outcome based on etiology of this presentation in congenitally malformed uterus - Sekulic, Slobodan; Stilinovic, Nebojsa; Baturan, Branislava; Krsman, Anita; Tesic, Igor; Vejnovic, Aleksandra; Petrovic, Djordje; Nikolasevic, Zeljka; Mijavec, Anna; Pesic, Vesna; Petkovic, Branka (Frontiers in Medicine, 2023)
Background Breech presentation (BP) results from at random filling of the intrauterine cavity, with an equal probability for a BP or cephalic presentation (CP). Each fetus in BP has its “pair” in CP randomly assumed CP. Direct comparison of BP and CP makes bias to less expressed differences between these two groups. It is therefore necessary to subtract the number of fetuses/newborns from the CP set that are identical to the number of fetuses/newborns in the BP set, with identical characteristics, and add this group to the BP set before comparing them to the rest of the CP fetuses/newborns in the matching process. Methods The procedure encompasses nine variables in pregnancies with a congenitally malformed uterus (CMU) identified at the Department of Obstetrics (1985–2014): gestational age, birth mass, birth length, head circumference, shoulders circumference, umbilical length, placental weight, newborn mass/newborn length ratio, and newborn mass/placental mass ratio. Firstly, the probability of BP was determined and its relation to gestational age, physical characteristics, and previous presentations. Then direct comparison as well as case–control matching of the CP and BP were performed. Case–control matching was based on either a single specific variable (M1) or all combined variables (M2). Findings 462 deliveries were identified with CMU. In 81 cases of multiparity, a fetal presentation was found to be an independent event regardless of the previous presentation, gestational age, and newborn physical characteristics. In four types of CMU with 337 deliveries (Bicornuate, Didelphys, Unicornuate, Arcuate), 9 variables with 36 instances of comparison were observed. M1 in 10 instances and M2 in 6 instances showed a statistically significant lower value of breech/random presentation compared with CP. CP have lower value in 2 instances in M1 and 1 in M2. Statistically significant differences were absent without the matching process. Interpretations The study confirms the maximum probability for the BP is 50%. The case–control matching procedure shows that it is able to detect the difference between the breech/random presentation and CP, while the classic method of direct comparison was unable to detect any differences. The outcome of the breech/random presentation in CMU should be evaluated with the described case–control matching procedure.